2023
DOI: 10.1101/2023.08.18.553804
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cooperation between bacteriocytes and endosymbionts drives function and development of symbiotic cells in mussel holobionts

Hao Chen,
Mengna Li,
Zhaoshan Zhong
et al.

Abstract: Symbiosis drives the adaptation and evolution in multicellular organisms. Modeling the function and development of symbiotic cells/organs in holobionts is yet challenging. Here, we surveyed the molecular function and developmental trajectory of bacteriocyte lineage in non-model deep-sea mussels by constructing a high-resolution single-cell expression atlas of gill tissue. We show that mussel bacteriocytes optimized immune genes to facilitate recognition, engulfment, and elimination of endosymbionts, and intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…In addition, the newly formed bacteriocytes of adult mussels also lose microvilli after being colonized by the symbionts of adjacent bacteriocytes (Wentrup et al, 2014). In our single-cell transcriptome study, we showed the participation of the sterol-related signaling pathway in the differentiation and maturation processes of mussel bacteriocytes (Chen et al, 2023). It is also noteworthy that the symbionts may control the function and development of host symbiotic organs in other symbiotic associations (Coon et al, 2017; Heath-Heckman et al, 2016; Nyholm and Mcfall-Ngai, 2021).…”
Section: Discussionmentioning
confidence: 90%
“…In addition, the newly formed bacteriocytes of adult mussels also lose microvilli after being colonized by the symbionts of adjacent bacteriocytes (Wentrup et al, 2014). In our single-cell transcriptome study, we showed the participation of the sterol-related signaling pathway in the differentiation and maturation processes of mussel bacteriocytes (Chen et al, 2023). It is also noteworthy that the symbionts may control the function and development of host symbiotic organs in other symbiotic associations (Coon et al, 2017; Heath-Heckman et al, 2016; Nyholm and Mcfall-Ngai, 2021).…”
Section: Discussionmentioning
confidence: 90%